Le système logique des hypothèses du Parménide de Platon dans le Commentaire de Georges Pachymère - Savoidakis, Georgios (Peitho. Examina Antiqua, 2025)
George Pachymeres’ Commentary on the second part of the Platonic dialogue Parmenides is from a codicological point of view a continuation of the lost part of Proclus’ Commentary, but it can be characterized in its essence as an autonomous exegetical effort by the polymath and Aristotelian philosopher that aims to deal with the demanding text of the Parmenidean hypotheses by codifying this argumentative system of Platonic dialectic. The purely logical identity of his interpretation, which is far from being influenced by the Neoplatonists’ metaphysical and theological approaches, is manifest through the logical system of the “24 arguments” that he borrows though from Proclus’ interpretation and tries to apply ad hoc to the Platonic system of hypotheses, following it as closely as he can. This article maps the landscape of Pachymeres’ hermeneutical effort, i.e., it tries to structure in a clear and complete scheme the skeleton of his methodological approach on the whole of Parmenides’ arguments, by seeking to establish the appropriate correspondences with Proclus’ logical system of the “24 dialectical modes” and by following step by step the course of the Byzantine commentator’s reasoning strategy, especially his ingenious adjustments between Plato’s demanding text and Proclus’ schematization-model. To what extent, then, would the skeleton of the system of hypotheses that Pachymeres reconstructs from the Proclean schemes be perfect or sufficiently robust? This problem is the starting point of the present study.